Computational fluid analysis of flow around a finite height circular cylinder using splitter plate - Mahjoub, Babak (2015)
Reducing drag force over non-streamlined bodies and controlling shedding of vortices behind them has been known as two major problems concerning flow control and aerodynamic studies. In the present study circular cylinder was chosen as the bluff body under investigation in a subcritical flow regime with Re = 3000. The cylinder is mounted to the surface, and possess variety of heights relative to its diameter, D, defined as cylinder aspect ratio AR with four variations of 3, 6, 9, and ∞ which is same as an infinite cylinder. Two Splitter plates are used as passive control apparatuses in the form of detached and mounted to the surface with no oscillation just with the same height as the cylinder and are mounted upstream and downstream of the cylinder. Splitter plates’ length were relative to the cylinder diameter specified as L1/D and L2/D. Likewise the gap between plates and the cylinder were defined relative to D as G1/D and G2/D. Variation of plates’ length and gap ratio resulted in different combinations in which the best possible choice for each AR has been sought in this study. This optimum state was defined as a combination where the most drag reduction and vortex suppression was found. Numerical solution has been deployed to measure the mean drag coefficient,Strouhal number and power spectra at the cylinder mid-height point. The effectiveness of the splitter plates were found in (i) reducing the drag which was mostly resulted by the upstream plate with its relative position as the dominant factor (comparing to its length ratio) and (ii) weakening or in some cases suppressing the vortex shedding, primarily as the result of implementation of downstream plate, while the key variable determined to be its length ratio unlike the upstream plate. Due to the presence of upstream plate at its optimum position (G1/D = 1.5) a reduction of 7.9% up to 16.8% has been achieved depending on the cylinder aspect ratio. Speaking about the aspect ratio, the longer the cylinder was, the more effect it took concerning drag reduction.